Association between sexual orientation and sexual contact with the incidence of human immunodeficiency virus (HIV) infection in Dr. Sardjito General Hospital, Yogyakarta - Imtihani, Hajar; Pudjiati, Angela Satiti Retno; Luthfiandi, Mochammad Rifky; Susetiati, Devi Artami (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Anal intercourse has been known to have a high risk of human immunodeficiency virus (HIV) transmission. The objective of this study was to evaluate the relationship between sexual orientation and the mode of sexual contact with the incidence of HIV infection. This was observational analytic study with cross sectional design. Subjects were new male patient who visited sexually transmitted infection (IMS) clinics at Dr. Sardjito General Hospital, Yogyakarta during 2016. Data were obtained from medical records. The HIV status was established from HIV rapid test and enzyme-linked fluorescent assay (ELFA). Data were analyzed using descriptive test and Pearson’s chi-squared test with significance level of p< 0.05. Among 167 subjects, 47.91% were in the age group 17 - 25 years old. Forty subjects (24%) had HIV positive status. The majority of subjects were heterosexuals (111 subjects (66.47%)), 43 subjects (25.75%) were homosexuals, and 13 subjects (7.8%) were bisexuals. HIV positive subjects were more common in homosexual groups than were heterosexual and bisexual (p